Italian regular immigration public policy: between exclusion, assimilation and integration - Calabrò, Marco (2019)
The work hereof intends to analyse some profiles of the regular migration phenomenon in Italy, by examining the most recent and relevant regulatory interventions in the welfare sector, both at state and local level. In particular, we intend to demonstrate that at least three approaches regarding the reaction of the legal system towards the access of the “other” currently co-occur in Italy. To this end, the first to be analyzed will be some examples of “exclusionary” operations will be analysed, which are based on the defense of the national cultural identity and the promotion of citizenship in its formal sense (C. Schmitt) – as they are found in several ordinances of local Authorities which restrict access to social rights for foreigners, as well as in some Regional Laws on social welfare. In addition to these exclusionary operations, even a second relational model will be examined, which is inclusive and assimilative, and therefore, opposite to the previous one, while it finds its most clear expression in the Integration Agreement, which an immigrant seeking a residency permit needs to adhere to. Finally, we will focus on a “third way”, inspired by an integrative approach based on the concept of permeable identity (J. Habermas), pursuant to which both they who welcome and who are welcomed are called upon to hold an attitude of mutual listening and understanding, not aimed at the incorporation of the weaker in the stronger, but rather, at the identification of common areas of dialogue that can lead to the best integration possible of two new identities (as both have made contact with the “other”). In this context, this paper aims at enhancing the role of the new public integration policies – especially at the local level – on sustainable development of current pluralist societies. In this regard, the legal instruments which are most effective in terms of developing an approach which is resilient and open-minded to communities that welcome regular immigrants, by facilitating the creation of (institutionalized and spontaneous) moments of dialogue and the sharing of knowledge of each other’s cultures.